1994
DOI: 10.1590/s0103-84781994000200004
|View full text |Cite
|
Sign up to set email alerts
|

Influência De Sistemas De Manejo De Solos E De Culturas Sobre Insetos Subterrâneos

Abstract: RESUMO Avaliou-se a influência de sistemas de manejo de solos e de culturas sobre insetos subterrâneos, em Cruz Alta, RS, de fevereiro de 1987 a agosto de 1990. Amostras de solo foram coletadas mensalmente e os insetos separados e identificados. Observou-se maior número de insetos no sistema de plantio direto (SMPD), com 62,0% do total. Larvas de elaterídeos, Acrolophus sp., Diloboderus abderus e Pantomorus sp., além de adultos de Ataenius sp., Blapstinus punctulatus e Cyrtomenus mirabilis, ocorreram com maior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
1
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
1
1
2
Order By: Relevance
“…Although the occurrence of insects of different species can be higher in a soil that has not been disturbed by farm equipment (Alvarado, 1979;Stinner & House, 1990;Silva et al, 1994aSilva et al, , 1994b, in this study it did not occur. In contrast, the extent of damage caused by white grubs on soybeans was similar in no-tillage and plowed areas.…”
Section: White Grub Versus Soil Managementcontrasting
confidence: 53%
See 1 more Smart Citation
“…Although the occurrence of insects of different species can be higher in a soil that has not been disturbed by farm equipment (Alvarado, 1979;Stinner & House, 1990;Silva et al, 1994aSilva et al, , 1994b, in this study it did not occur. In contrast, the extent of damage caused by white grubs on soybeans was similar in no-tillage and plowed areas.…”
Section: White Grub Versus Soil Managementcontrasting
confidence: 53%
“…Studies conducted by Silva et al (1994a) showed that soil management system affected the species differently. According to these authors, no-tillage favored the survival of saprophytic and occasionally rhizophagous species, such as D. abderus, which needs mulch for oviposition and initial development.…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, apresenta alto potencial de produção de matéria seca (MS), em média de 7 a 10 t/ha, dependendo das condições climáticas, cultivar e fertilidade do solo, podendo chegar até 20 t/ha de matéria seca (BOGDAN, 1977 Podemos ver que as ordens de díptera e himenóptera e hemíptera correspondem a quase 73% dos insetos coletados. ALL et al, 1979;SILVA et al, 1994…”
Section: Conclusõesunclassified
“…Práticas que contribuem para a manutenção ou aumento do teor da umidade no solo, como irrigação, quando viável, e o sistema de plantio direto também podem influenciar a incidência da praga, já que a oviposição diminui em solos com maior teor de umidade COSTA, 1993;SILVA et al, 1994;GALLO et al, 2002). , 1980;TIPPINS, 1982;MOAR et al, 1995).…”
Section: Manejo Da Pragaunclassified